Clinical Outlook for Type-1 and FOXP3+ T Regulatory Cell-Based Therapy - Gregori, Silvia; Passerini, Laura; Roncarolo, Maria-Grazia (Frontiers in Immunology, 2015)
T regulatory cells (Tregs) are subsets of T lymphocytes specialized in modulating antigen-specific immune responses in vivo. Hence, Tregs represent an ideal therapeutic tool to control detrimental immune reactions. Based on solid pre-clinical results, investigators started testing the safety and efficacy of Treg-based therapies in humans. Despite promising results, a number of issues remain to be solved. We will discuss the results obtained from clinical trials and the challenges and risks we are facing in the further development of Treg-based therapies.